(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2014)
People do not have the food needed to meet their basic needs in many parts of the world. That is, they may be forced to eat what they have access to or what the circumstances provide for. Therefore, poverty and scarcity play a large role in the choices that many people have to make on a daily basis around produce and maybe an underlying cause for their decision to consume cheap, processed food. On the contrary, there is a significant body of literature that describes the typical patterns of hyper-consumerism in the United States even though people do not know where their food comes from. More specifically, they do not have a relationship with farmers, they do not know the farmworkers, and they do not recognize the dangers associated with fertilizers, herbicides, and pesticides. This, in turn, may lead them into making poor nutritional choices regardless of their socioeconomic status. This scenario may also apply to people who chose to live a vegetarian or vegan lifestyle. However, there is an emerging trend of local and organic farming and mindfulness around personal and shared dietary wellness. This trend renews the cultural memories, intergenerational knowledge, traditions, cultural ceremonies and narratives of people from around the world who contribute to living a more sustainable (and healthy) lifestyle in relation to food. I will argue for a socioecological movement that serves to strengthen principles and characteristics for food mindfulness and the implication of creating heuristics or experiential heuristics for mindful eating. This theory is based on my work as an organic market farmer for two years. It mediates the hegemony of neoliberalism and hyper-consumerism and works towards ecojustice and food activism in science education.